Brain activations while processing degraded speech in adults with autism spectrum disorder. (12th February 2021) - Lin, I-Fan; Itahashi, Takashi; Kashino, Makio; Kato, Nobumasa; Hashimoto, Ryu-ichiro
Abstract: Individuals with autism spectrum disorder (ASD) are found to have difficulties in understanding speech in adverse conditions. In this study, we used noise-vocoded speech (VS) to investigate neural processing of degraded speech in individuals with ASD. We ran fMRI experiments in the ASD group and a typically developed control (TDC) group while they listened to clear speech (CS), VS, and spectrally rotated VS (SRVS), and they were requested to pay attention to the heard sentence and answer whether it was intelligible or not. The VS used in this experiment was spectrally degraded but still intelligible, but the SRVS was unintelligible. We recruited 21 right-handed adult males with ASD and 24 age-matched and right-handed male TDC participants for this experiment. Compared with the TDC group, we observed reduced functional connectivity (FC) between the left dorsal premotor cortex and left temporoparietal junction in the ASD group for the effect of task difficulty in speech processing, computed as VS-(CS + SRVS)/2. Furthermore, the observed reduced FC was negatively correlated with their Autism-Spectrum Quotient scores. This observation supports our hypothesis that the disrupted dorsal stream for attentive process of degraded speech in individuals with ASD might be related to their difficulty in understanding speech in adverse conditions. Highlights: Functional connectivity (FC) for speech process in adverse conditions is decreased in autism. This reduced FC spans between the left dorsal premotor cortex and left temporoparietal junction. This reduced FC is negatively correlated with their autistic symptoms.